The Determinants of Rate of Return Deposits In Islamic Banks - Ahmad Al-Harbi (Journal of Finance and Islamic Banking, 2019)
This article aims to identify the determinates of the rate of return on deposits in Islamic banks. The study, according to the best of my knowledge, is the first study to investigate the factors affecting the rate of return in Islamic banks using cross-country data with a large sample of banks and for a prolonged period. To achieve its aim, the author used data from almost all Islamic banks in the world for a 20-year period (1989-2008). The data were analyzed using a two-way fixed-effect model. The empirical results demonstrate that capital adequacy (default risk), credit risk, age, economic growth, and concentration significantly and negatively influenced the return on deposits in Islamic banks. The results also suggest that foreign ownership, size, inflation, and oil prices had significant and positive effects on the rate of return. Moreover, the results indicated that deposit insurance (positive), interest rates (positive), and deposit growth (negative) are not determinants of the rate of return in Islamic banks.Â